Respuesta :
Answer:
A. 31
B. 4n - 1
Step-by-step explanation:
A + (n-1)d
(a is the first term of the sequence, and d is the common difference)
= 3 +(8 - 1)4
= 3 + 7(4)
= 3 + 28 = 31
= a + (n-1)d
= 3 + (n-1)4
= 3 + 4n - 4
=4n - 4 + 3
= 4n - 1
Answer:
see explanation
Step-by-step explanation:
Note there is a common difference d between consecutive terms, that is
d = 7 - 3 = 11 - 7 = 15 - 11 = 19 - 15 = 4, thus sequence is
3, 7, 11, 15, 19, 23, 27, 31 ← with 8 th term = 31
The sequence is arithmetic with n th term
[tex]a_{n}[/tex] = a₁ + (n - 1)d
where a₁ is the first term and d the common difference
Here a ₁ = 3 and d = 4, thus
[tex]a_{n}[/tex] = 3 + 4(n - 1) = 3 + 4n - 4 = 4n - 1